PPPH frontliners send students back to hometowns - Mohd Ferdaus, Musa (2020)
Kuantan, 28 May 2020 - Coordinating over 100 trips of university and external buses to send students to respective hometowns from 30 April until 14 May 2020 was an invaluable experience for the task force and drivers at the Department of Property Management & Development (PPPH).